Detection of BRAFV600E Biomarker In Patients With Colorectal Cancer Using Immunohistochemical Techniques / Clinico-Pathological Study - Alrubaiaee, Seror Abdul Kareem Turkan; Jawad Kadhim Al-taee , Thaeer (Journal of the Faculty of Medicine Baghdad, 2022)
Background : Colorectal cancer (CRC) is the 4th common gastrointestinal cancer. (BRAFV600E) is a member of RAF family of serine/threonine protein kinases that function to regulate the (MAPK) / (ERK) pathway. BRAFV600E mutated CRC are associated with right-sided primary tumors, older women and high-grade tumors. Aims of the study: Study the immunohistochemical expression of BRAFV600E biomarker in a sample of Iraqi patients with colorectal cancer and the correlation of BRAFV600E expression with other clinicopathological variables such as patient’s age and tumor grade. Materials and Methods : in this prospective study a total of 90 colorectal cases of a sample of Iraqi patients were collected from teaching labs of AL-Yarmouk Teaching Hospital including 60 cases of colorectal carcinoma and 30 cases of colorectal adenoma. Result: BRAFV600E biomarker was positive in 16.6% of colorectal carcinoma group and negative in colorectal adenoma group. Conclusions: BRAF expression was higher in older patients ages & higher tumor stages and there is no expression of BRAFV600E in adenoma cases.